2020
DOI: 10.1088/1361-648x/abc4ce
|View full text |Cite
|
Sign up to set email alerts
|

Impact of defects on photoexcited carrier relaxation dynamics in GeSn thin films

Abstract: We report the results of a study that was conducted to investigate the recombination paths of photoexcited charge carriers in GeSn thin films. The charge carrier lifetime was predicted as a function of temperature from a description of photoconductivity transients, assuming co-influence of Shockley–Read–Hall and radiative carrier recombination paths. We identify that dislocations are the source of a band of electronic states with the highest occupied state at E V + (85÷90) meV that acts as Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This peak is significantly related to the dislocations/defects states formed in the forbidden bandgap near the GeSn/Ge interface. Previously, it has been reported that the deep defect levels existed at ∼0.55 and ∼0.62 eV for Ge 0.968 Sn 0.032 and Ge 0.96 Sn 0.04 at 83 K, respectively, which are consistent with this work [19]. Similarly, defect-related peaks were observed in GeSn with Sn contents from 1.2% to 5.0% in [39].…”
Section: Photoluminescence (Pl) and Photoconductivity (Pc)supporting
confidence: 91%
See 2 more Smart Citations
“…This peak is significantly related to the dislocations/defects states formed in the forbidden bandgap near the GeSn/Ge interface. Previously, it has been reported that the deep defect levels existed at ∼0.55 and ∼0.62 eV for Ge 0.968 Sn 0.032 and Ge 0.96 Sn 0.04 at 83 K, respectively, which are consistent with this work [19]. Similarly, defect-related peaks were observed in GeSn with Sn contents from 1.2% to 5.0% in [39].…”
Section: Photoluminescence (Pl) and Photoconductivity (Pc)supporting
confidence: 91%
“…To deeply understand the carrier dynamic, many efforts have been conducted via the diverse methods [9,19,20]. Most experiments have been conducted at low temperature to observe the various carrier behaviors sensitively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct-bandgap GeSn alloys are promising group-IV semiconductors for monolithic integration of light-emitting and photosensitive devices on silicon . In recent years, significant efforts have been made to produce GeSn alloys with high crystalline quality, surface morphology, optical properties, and transport properties. Moreover, various GeSn-based optoelectronic and photonic devices such as mid-infrared photodetectors, light-emitting diodes, and continuous-wave and pulsed lasers , have been designed and tested. Their successful design requires the realization of direct bandgap GeSn alloys due to prospects of achieving high absorptivity and high emission efficiency in the IR region.…”
Section: Introductionmentioning
confidence: 99%
“…This PL peak point of 0.57 eV in Figure 74(a) is significantly related to trap states near GeSn/Ge. Previously, deep defect states were observed at 0.55 and 0.62 eV for Ge0.968Sn0.032 and Ge0.96Sn0.04 at 83 K, respectively [149]. Also, defect-related PL peaks were observed in thin GeSn films with Sn contents from 1.2 to 5.0% [150].…”
Section: Photoluminescence and Photoconductivitymentioning
confidence: 96%